Special GRIT chair for Muhammad Amirul - UMP, PNC (2019)
Eight-year old Muhammad Amirul Fikri Mohamad Fazir’s face lit up with joy upon receiving a specially-designed chair called GRIT Chair that was made by a group of Universiti Malaysia Pahang (UMP) students and lecturers from Faculty of Mechanical Engineering.